Characterization of second-order bands in Raman scattering spectra of lead phthalocyanine thin films - Gorishnyi, M.P.; Fesenko, O.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
The structure, optical absorption (500…950 nm), and resonance Raman spectra (within the range 100…3000 cm⁻¹) of lead phthalocyanine (PbPc) thin solid films with a thickness of 190 nm were studied. The films were deposited using thermal evaporation in a vacuum of 6.5 mPa onto silica substrates held at room temperature. It was found that in the process of depositing the PbPc thin solid films, monoclinic and triclinic PbPc crystallites were grown, and the amount of crystallites in the triclinic phase in the as-deposited PbPc films was approximately two times less than that in the monoclinic phase. The resonance Raman spectroscopy, with application of the He-Ne laser line 632.8 nm as an excitation source, was used for studying the 190-nm-thick PbPc films. Due to resonance enhancement, the second-order Raman spectrum of PbPc films within the region 1700…2950 cm⁻¹ was successfully registered and analyzed for the first time. It has been shown that the second-order PbPc Raman spectrum is mainly formed by the overtones and combination modes of B₁ symmetry fundamental vibrations. The second-order Raman region of 2550…2900 cm⁻¹ appeared to be highly specific for PbPc and could be used for its identification along with the fingerprint region of fundamental vibrational modes. Досліджено структуру, спектри оптичного поглинання (500…950 нм) та резонансні КРС (100…3000 см⁻¹) тонких твердих плівок фталоціаніну свинцю (PbPc) товщиною 190 нм. Плівки осаджено термічним випаровуванням у вакуумі 6,5 мПа на витримані при кімнатній температурі кварцові підкладки. Установлено, що в процесі осадження тонких плівок PbPc виросли моноклінні та триклінні кристаліти PbPc, причому кількість кристалітів триклінної фази у свіжонанесених плівках PbPc була приблизно в два рази меншою. Для дослідження тонких твердих плівок PbPc товщиною 190 нм була застосована резонансна раманівська спектроскопія з використанням He-Ne лазерної лінії 632,8 нм як джерела збудження. Завдяки резонансному підсиленню вперше було успішно зареєстровано та проаналізовано спектр КРС плівки PbPc другого порядку в області 1700–2950 см⁻¹. Було показано, що спектр КРС другого порядку PbPc формується переважно з обертонів та комбінаційних мод основних коливань симетрії B₁. Спектральна ділянка 2550–2900 см⁻¹ спектрів КРС виявилася надзвичайно специфічною для PbPc і може бути використана для його ідентифікації разом із областю відбитків пальців основних коливальних мод.